2020
DOI: 10.36778/jesya.v3i2.191
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kemudahan Informasi Dan Kualitas Informasi Terhadap Keputusan Bersedekah Di Masjid – Masjid Kota Batam

Abstract: Penelitian ini bertujuan untuk mengetahui sejauh mana pengaruh kenyamanan informasi dan kualitas informasi berpengaruh pada keputusan untuk memberikan amal. Metode analisis yang digunakan dalam penelitian ini adalah analisis kuantitatif dengan metode analisis regresi berganda. Sebelumnya dilakukan uji validitas, uji reliabilitas menggunakan nilai koefisien Alpha Cronbach. Berdasarkan hasil analisis yang dilakukan, dapat disimpulkan bahwa secara parsial (uji-t) variabel Kemudahan Informasi berpengaruh signifika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…This beach is called Gope, because tourists visiting the beach only need to Islamiconomic: Jurnal Ekonomi Islam Vol.12 No.1 January -June 2021 pay 500 rupiah for two-wheeled vehicles and 1000 rupiah for four-wheeled vehicles. The validity test according to Ghozali (2011) in Faisal and Sari (2020) aims to measure whether a questionnaire is valid or not. An item is said to be valid if the statement on the questionnaire is able to reveal something that will be measured by the questionnaire (Faisal & Sari, 2020).…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This beach is called Gope, because tourists visiting the beach only need to Islamiconomic: Jurnal Ekonomi Islam Vol.12 No.1 January -June 2021 pay 500 rupiah for two-wheeled vehicles and 1000 rupiah for four-wheeled vehicles. The validity test according to Ghozali (2011) in Faisal and Sari (2020) aims to measure whether a questionnaire is valid or not. An item is said to be valid if the statement on the questionnaire is able to reveal something that will be measured by the questionnaire (Faisal & Sari, 2020).…”
Section: Results and Analysismentioning
confidence: 99%
“…The validity test according to Ghozali (2011) in Faisal and Sari (2020) aims to measure whether a questionnaire is valid or not. An item is said to be valid if the statement on the questionnaire is able to reveal something that will be measured by the questionnaire (Faisal & Sari, 2020). The validity test was carried out using the SPSS version 23 program, the test results can be seen in the following table: Based on the results of the validity test in the table above, it is known that the rcount value of all question items is greater than r table (0.220), so it can be concluded that the question items in the questionnaire are all valid.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Uji validitas menurut (Ghozali, 2005) bertujuan untuk mengukur sah atau valid tidaknya suatu kuesioner. Suatu item dikatakan valid jika pernyataan pada kuesioner mampu untuk mengungkapkan sesuatu yang akan diukur oleh kuesioner tersebut (Faisal & Sari, 2020) Berdasarkan hasil uji validitas pada tabel 6 di atas diketahui, nilai rhitung seluruh item pertanyaan lebih besar dari rtabel (0.220), sehingga dapat disimpulkan bahwa item pertanyaan dalam kuesioner seluruhnya valid.…”
Section: Uji Validitasunclassified
“…Uji Reliabilitas menurut Ghozali (2011) dalam Faisal dan Sari (2020) dilakukan untuk menguji konsistensi pernyataan responden dari waktu ke waktu (Faisal & Sari, 2020) Berdasarkan hasil uji reliabilitas pada tablel 7 di atas, diketahui bahwa nilai cronbach's alpha variabel pendapatan (X1) lebih besar dari rtable (0.685 > 0.220), nilai cronbach's alpha variabel religiusitas (X2) lebih besar dari rtable (0.637 > 0.220), nilai cronbach's, alpha variabel trust (X3) lebih besar dari rtable (0.813 > 0.220), dan nilai cronbach's, alpha variabel minat membayar zakat (Y) lebih besar dari rtable (0.733 > 0.220). Dengan demikian dapat disimpulkan seluruh variabel dalam penelitian ini reliabel dan handal.…”
Section: Uji Reliabilitasunclassified